2021
DOI: 10.3389/fcell.2021.735307
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Signatures of Airway Epithelium Infected With SARS-CoV-2: A Balance Between Anti-infection and Virus Load

Abstract: COVID-19 pneumonia requires effective medical therapies. However, it is a challenge to find therapeutic drugs that not only inhibit viral replication, but also inhibit the accompanying cytokine storm and maintain an appropriate immune response. In this study, the effects of SARS-CoV-2 on gene expression in lung epithelial cells from patients with COVID-19 were systematically evaluated with bioinformatics analysis methods. Transcriptome expression specific to bystander (exposed but uninfected) and infected cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…A high viral load in epithelial cells was not implicated in a severe ARDS outcome or poor recovery. On the other hand, gene signatures related to increased viral load fall into the mild or moderate group [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high viral load in epithelial cells was not implicated in a severe ARDS outcome or poor recovery. On the other hand, gene signatures related to increased viral load fall into the mild or moderate group [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is challenging to find therapeutic drugs that inhibit viral replication and cytokine storms yet maintain an effective anti-viral immune response. A study by Meng L et al identified that a high viral load does not necessarily imply a low immune response [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…To screen for the crucial survival-related factors, the DEGs from the two risk groups were analysed with Wilcoxon's test and were enriched for the KEGG pathway analyses (Figures 3(a) and 3(b) ). GSEA KEGG pathway analyses were done using webgestalt.org website [ 8 ]. Of those pathways, PPAR signaling was upregulated and the IL17 signaling was decreased in the high risk group (Figures 3(c) and 3(d) ).…”
Section: Resultsmentioning
confidence: 99%
“…Statistics investigations were carried out with R software (version 3.6.0). Kaplan-Meier tests and ROC analysis were performed as we described previously [ 8 , 9 ]. In brief, we utilized the “survivor” and “survROC” software packages in both analyses [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…Statistical analyses were carried out using R software (version 3.6.0). Kaplan-Meier tests and ROC analysis were performed as described previously ( 13 , 14 ). In brief, the “survivor” and “survROC” software packages were utilized for both types of analyses ( 15 ).…”
Section: Methodsmentioning
confidence: 99%